Peminjaman Kata (Isti’arah) dalam Al Quran - Ridwan Ridwan (UIN Maulana Malik Ibrahim Malang, 2007)
Isti'arah is borrowing word (loan words) used in other words because of some factors. Alquran is hardly understood only based on linguistic principles, but it must also be studied using other approaches, such as literary approach that is often used in contemporary studies, well known as literary approach to Alquran. Isti'arah is a part of literature. Alquran with all of its miracles contains literary aspects that are undeniable for those who understand it. Therefore, Moslem scholars agree that Isti'arah in Alquran exactly aims at earning attention from the hearers and the readers of Alquran, in turn, increasing our belief in the miracle of Alquran in literary aspect. For instance the word